A novel mutation in DNAH17 is present in a patient with multiple morphological abnormalities of the flagella. Issue 3 (September 2021) - Zheng, Rui; Sun, Yongkang; Jiang, Chuan; Chen, Daijuan; Yang, Yihong; Shen, Ying
Abstract: Research question: Asthenoteratospermia is characterized by malformed spermatozoa with motility defects, which results in male infertility. Multiple morphological abnormalities of the sperm flagella (MMAF) is a hallmark of asthenoteratospermia. The genetic causes of MMAF, however, are unknown in about one-third of cases. Which other MMAF-associated genes are waiting to be discovered? Design: Whole-exome sequencing was conducted to identify causative genes in a man with MMAF. Immunofluorescence staining and western blot were applied to assess the pathogenicity of the identified variant. Intracytoplasmic sperm injection (ICSI) was used to assist fertilization for the patient with MMAF. Result: Sanger sequencing of the family demonstrated that the infertile man carried a homozygous DNAH17 variant (c. 4810C>T [p.R1604C]). The obviously decreased DNAH17 expression was observed in HEK293T cells transfected with MUT- DNAH17 plasmid compared with cells with WT- DNAH17 plasmid. Immunofluorescence analysis showed that this mutation induced significant decrease in DNAH17 expression, which negatively affected the DNAH8 expression in the patient's spermatozoa. Moreover, the outcome of ICSI in the patient was unsuccessful. Conclusion: Our study revealed a novel homozygous missense mutation in DNAH17 involved in MMAF phenotype. The finding of the novel mutation in DNAH17 enriches the gene variant spectrum of MMAF, further contributing to diagnosis, genetic counselling and prognosis for male infertility.